Relationship between Histopathological Subtypes of Intracranial Astrocytoma Patients - Mahmud, Fazle; Nath, Haradhan Deb; Barua, Kanak Kanti; Hossain, Afzal (Bangladesh Journal of Neuroscience, 2014)
Background : The study was carried out in the department of neurosurgery, BSMMU, Dhaka during the period of July 2003 to June 2005. Objective: This study was done to elucidate the relationship between age groups and histopathologicas subtypes in case of intracranial astrocytoma patients. For this purpose, a total number of 44 cases were studied. Results: The mean age of all the patients was 33.1 years (range:1-65 years). The highest incidence was found in the age group of 20 years or below group. Male were more commonly effected than female. WHO grade I astrocytoma was the commonest type. Mean age of low grade astrocytoma (WHO grade II) and glioblastoma were nearly similar to other studies, but the mean age of presentation of grade I astrocytomas patients was little late and for anaplastic actrocytoma a little early in comparison to other study. Conclusion: This showed subtype of astrocytoma has definitive relation to age. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 87-93 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17575